--Phana-- Sommāi Huntrakūn - Sommāi Huntrakūn, 1918-1993 (Khunying Somsī Huntrakūn, 1993)
Cremation volume for Sommāi Huntrakūn, 1918-1993, a former finance minister of Thailand; comprises his biography, condolences and reproduction of caricatures and news columns from Thai dailies about the crematee.